3262 Determining the association of acculturation, community identity and discrimination on cancer screening rates and quality of life among underserved populations. (27th March 2019) - Rodriguez Berrios, Maria D; LeClair, Amy; Breeze, Janis; Reisenger, Sarah; Gonzalez, Evelyn; Oliveri, Jill; Paskett, Electra; Freund, Karen
Abstract : OBJECTIVES/SPECIFIC AIMS: To determine the association of participant's characteristics and socio-cultural factors including acculturation, community identity and discrimination with the adherence to cancer screening guidelines and participants' quality of life. METHODS/STUDY POPULATION: As part of the Cancer Disparities Research Network pilot cohort, the study recruited 333 participants across four sites: Boston Chinatown, African American communities in Philadelphia, and Hispanic communities in Columbus, and rural white communities in Appalachia, Ohio. Enrolled participants were eligible if they were 40 to 74 years old, did not live in a nursing home or other facility, and had no prior invasive cancer diagnosis. Additionally, each participant met at least one of the following criteria: living in a medically underserved area, having low literacy, low income (defined as 100% of the 2015 Federal Poverty Level FPL according to 2015 FPL Guidelines), or being uninsured or receiving subsidized health insurance coverage. Participants completed a baseline survey of demographic data, health status, including health behaviors and risk factors to cancer, Primary Care Physician (PCP) status and most recent breast, cervical, prostate, skin and colorectal cancer screenings. Information related to discrimination, acculturation or adaptation, and sense of belonging to their community was collected using validated instruments. RESULTS/ANTICIPATED RESULTS: Of the 333 participants enrolled in the study, 65.5% were women, 14.1% were 40-50 years of age, 59.8% were 51-64 years, and 26.1% were 65-74. The cohort was racially and ethnically diverse: 8.4% of participants identified as Hispanic, 30.3% as non-Hispanic White, 31.2% as non-Hispanic Black, 29.4% as non-Hispanic Asian, and 0.6% as Other. 62.2% spoke English, 8.1% Spanish, and 29.7% Chinese as their primary language. Low incomes were common: 33.6% reported incomes 15, 000 or less, and 25.8% reported incomes between 15, 000 and 24, 999. Overall adherence to USPSTF guidelines on cancer screening rates was 77.9% for breast cancer, 71.1% for cervical cancer, and 67.7% for colorectal cancer. Analyses will present the association of acculturation, community identity, and discrimination with cancer screening and quality of life measures. DISCUSSION/SIGNIFICANCE OF IMPACT: This study will promote the increase of cancer disparities research, and reinforce the importance of inclusion and increased recruitment of diverse populations in future studies. By determining the potential factors associated with cancer disparities among minority populations, it may provide new information for clinicians to have more cultural sensitivity addressing potential disparities in the clinical setting. It will also promote the creation of more tailored interventions and programs to deliver adequate healthcare among these populations.